Occupational exposure and health of wildland firefighters: protocol for a systematic review
The frequency of forest fires has increased in recent years. This phenomenon has led to an increase in the difficulty of fighting them and an increase in the occupational exposure of firefighters. This study aims to carry out a systematic review protocol to obtain information on firefighters' occupational exposure on the fire front. A protocol was carried out following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses: PRISMA Statement guidelines. There were no age, gender or publication date restrictions for including articles within the scope of firefighter samples. The study aimed to understand all the risks to which firefighters are exposed when fighting forest fires and their relationship with the onset of occupational diseases. Thus, all studies with laboratory or real-time monitoring, using samples of firefighters, and which carried out evaluations that made it possible to identify exposure risk factors and their relationship with occupational activity were included. This list makes it possible to verify all the studies carried out up to the date of the review on this subject and to guarantee a contribution to improving knowledge in this area of research.